Revisiting transboundary water allocation in the Incomati: emerging evidence from a CGIAR modelling effort - van der Merwe, S.; Fakudze, B.; Lautze, Jonathan F. (Water, Energy & Food Security Resource Platform, 2025)
This article presents a transboundary water modeling initiative in the Incomati River Basin, engaging stakeholders from South Africa, Eswatini, and Mozambique to explore alternative water allocation scenarios in light of climate change and growing demand.